THE ROLE OF CURRICULUM MANAGEMENT IN PROMOTING STUDENT LITERACY CULTURE - Sopiyulloh, Oop; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this study was to objectively and empirically analyze: Curriculum planning in improving literacy culture; Curriculum organization in improving literacy culture; Curriculum implementation in improving literacy culture; Curriculum evaluation in improving literacy culture. This study was conducted using a descriptive qualitative approach, viewed from the perspective of Curriculum Management in Improving Literacy Culture, with a qualitative approach in accordance with the actual situation. The results of the study showed that: Curriculum planning in improving literacy culture includes: Determining the curriculum foundation; Determining the curriculum objectives; Determining the curriculum content; Determining the learning methods and strategies; Determining the learning resources; Determining the curriculum assessment or evaluation strategy. Curriculum organization in improving literacy culture includes: Organization of the Curriculum Development Team; Grouping of subjects. Curriculum implementation in improving literacy culture includes: Organizing Al-Qur'an literacy programs; Increasing the effectiveness of the library; Organizing a kultum program before the congregational Friday prayer; Organizing a YouTube podcast channel; Organizing a madrasa student magazine program; Making scientific papers for students as one of the graduation requirements; Curriculum evaluation in improving literacy culture includes: Daily evaluation, with evaluation techniques in the form of observation and assessment; Monthly evaluation, with evaluation techniques in the form of mapping and Focus Group Discussion (FGD); Semesterly evaluation, with evaluation techniques in the form of assessment, questionnaires, mapping, supervision, and Focus Group Discussion (FGD); Annual evaluation with evaluation techniques including questionnaires, mapping, and Focus Group Discussion (FGD).